Determinants Of Stress Levels In Nurses Tgk Chik Di Tiro Hospital Year 2023 - Nelliyana Nelliyana; Donal Nababan; Evawani M. Silitonga (SEAN Institute, 2023)
Stress experienced by nurses is stress that is obtained or experienced at work which is included in work stress. This study aims to determine the factors that influence the stress level of nurses who work in the inpatient room at Hospital. This research is an analytical study with cross sectional. The population in this study were all nurses totaling 115 people. The research sample uses the Slovin Formula so that the number of samples is 54 people. Data collection was obtained through a questionnaire. The data processing process starts from editing, coding, and tabulation. Data analysis consisted of univariate and bivariate analysis with Chi Square test. Multivariate analysis with simple linear regression test. Research results There is a relationship between workload and stress levels in inpatient nurses based on the results of the chi-square statistical test analysis obtained p value = 0.000 <0.05. There is a relationship between work fatigue and stress levels in inpatient nurses based on the results of the chi-square statistical test analysis obtained p = 0.000 <0.05. There is a relationship between work shifts and stress levels in inpatient nurses based on the results of the chi-square statistical test analysis obtained p value = 0.000 <0.05. There is a relationship between age and stress levels in inpatient nurses based on the results of the chi-square statistical test analysis obtained p value = 0.000 <0.05. There is a relationship between job security and stress levels in inpatient nurses. Based on the results of the chi-square statistical test analysis, the value of p = 0.000 <0.05 was obtained. The most dominant factor influencing the stress level of inpatient nurses at Hospital is job security. As for suggestions for nurses at Hospital in order to improve self-coping so that stress does not occur at work, especially stress occurs because of job security.